FePS3-MoS2 p-n junctions for broadband optoelectronics - Mei Xian Low; Taimur Ahmed; Saurabh K. Saini; Majid Panahandeh-Fard; Joao O. Mendes; Anthony S. R. Chesman; Chenglong Xu; Joel Van Embden; Lan Wang; Mahesh Kumar; Sharath Sriram; Madhu Bhaskaran; et al. (npj 2D Materials and Applications)
Abstract Broadband photodetectors and photovoltaic devices are crucial components in various optoelectronic applications, spanning self-powered photodetectors, solar energy harvesting and optical imaging systems, where optical sensitivity and efficient charge carrier generation are paramount. Two dimensional (2D) materials can be used to form p-n junctions for these applications, without crystal lattice or grain boundary constraints, which are common issues in bulk semiconductors. However, a key challenge lies in developing 2D heterojunctions that can efficiently harvest light across a broad spectrum while maintaining high charge separation. Here, we report heterojunctions of iron phosphorus trisulfide (FePS3) and molybdenum disulphide (MoS2) as the p- and n-type materials, respectively, demonstrating broadband photoresponse and photovoltaic behaviour. The results reveal that the FePS3-MoS2 heterojunctions form a Type-II band alignment, which not only enhances charge separation at the interface but also leads to faster relaxation times as compared to the individual materials. As such, enabling a robust photovoltaic and photoresponse across the visible spectrum. Notably, the heterojunctions exhibit a short-circuit current density of ~0.29 mA/cm² under visible light and outperform similar two-material heterostructures. These heterojunctions also demonstrate potential for translation onto flexible platforms by maintaining a comparable optoelectronic performance. This opens up opportunities for engineering flexible and self-driven optoelectronic devices, which is beneficial for smart wearable technology.